The Requirements of the International Solidarity for a Sustainable Development in Developing Countries - Mulami K, Alphonse NKONGOLO (European Journal of Sustainable Development, 2017)
The question is how to realize under what conditions international solidarity could be acceptable and could contribute to the truly sustainable development of the countries of the third world. What are the requirements (ethical, scientific, environmental ...) of a truly sustainable development? It will be straightforward to demonstrate that any international solidarity of a project (i.e. any multilateral or bilateral financing, etc.) that does not provide a chain of values in its execution, evidencing a clear theory of change, this international solidarity will be declared ineffective, and therefore rejected by Third World countries, since it does not guarantee in any way sustainable development, but is only capable of favoring all other evils (corruption, corruption, etc.). ...) that Dambisa Moya had to stigmatize in a book "Help fatale". Keywords: International solidarity. Sustainable development. Developing countries